An Assessment of the World Experience and of the Characteristics of the Transport Infrastructure of Cities that Have Hosted the Soccer World Cup - Evgeniya V. Vidishcheva; Dmitriy S. Ageenko (Centre for Behaviour and Wellness Advocacy, 2015)
This article features an analysis of the world experience and of the characteristics of transport servicing of large-scale world soccer tournaments, conducted with a view to identifying potential bottlenecks in transport infrastructure, determining the necessary amount and types of transport vehicles engaged in transporting World Cup visitors and participants, proposing recommendations on transport servicing, and helping to take timely measures to make relevant adjustments as part of staging a portion of the 2018 FIFA World Cup in the city of Sochi. The experience of staging the Sochi Winter Olympics will help use the city's existing transport infrastructure as effectively as possible. Among some of the most crucial conditions for the success of staging a large-scale event are the availability of sufficient territorial space for the unimpeded and safe movement of large masses of people around the stadium and the stadium's proximity to the key elements of transport infrastructure, as well as to hotels and the heart of the city's social and commercial life. What complicates the transport planning of major soccer events is the tough-to-predict nature of transport traffic due to the movement of both the national teams and the fans and the highly uneven volumes of passenger and freight traffic during the event. This provides a rationale for instituting additional requirements for the traffic capacity of transport infrastructure, its reliability, safety, and efficiency on the whole.